Development of electrolyzed water sanitation program for SME frozen meat patty industry - Khalid, Nurul Izzah (2021)
Sanitation (a process of cleaning and disinfection) of food contact surfaces is an essential procedure in the frozen meat industry. In all countries, sanitation is mandatory in the food industry to ensure food safety throughout the production processes as prescribed by their food law. Implementing a suitable sanitation program (depending on the size and complexity of the food processing) is part of the general pre-requisite for food safety management. Meeting relevant legislation requirement for sanitation is important for compliance reasons; it is also beneficial to the success of the food business. Implementation of an effective sanitation program can maintain a clean work environment and produce high-quality and safe food products. The frozen meat industries, especially Small and Medium Enterprises (SMEs), are facing difficulties in implementing a good sanitation program. Budget restriction, limited production area, and lack of knowledge on the latest and effective sanitation technology (either cleaning tools or sanitation solutions) are the hurdles for sanitation efforts. Suitable cleaning tools and food-grade sanitation solutions are expensive and can burden Food SMEs. Therefore, the development of innovative green sanitation may result in cost savings and the elimination of harsh chemicals used in the food factory. Electrolyzed water (EW) is classified as a green sanitation solution. The main objective of this work is to propose a green sanitation technology based on industrial-based and laboratory-based studies which can be implemented in the frozen meat industry. The study was initiated with evaluation studies of the current sanitation program at a local SME factory (Factory X) that produces frozen meat patty. To evaluate the factory's sanitation process, interviews with the top-to-bottom workers and several visits were conducted. In particular, the purpose was to determine current cleaning tools, sanitation solutions, sanitation steps/procedures used, and problems faced by Factory X. In designing a good sanitation program, several factors were considered: 1) cleaning tools, 2) sanitation parameters (time, temperature, and water jet pressure), and 3) sanitation solutions. Several sanitation programs were tested using a portable cleaning unit and industrial cleaning brushes. The efficiency of the portable cleaning unit at different nozzle distances (10 cm and 20 cm), sanitation times (30 s and 120 s), and temperatures (20C and 65C) in reducing different foodborne pathogens (Escherichia coli, Listeria monocytogenes, and Salmonella enteritidis) were evaluated. A preliminary study has revealed that using a portable cleaning unit was not a cost-effective solution due to commercial sanitation solutions and heating costs. Accordingly, new technology was proposed to integrate an EW generator into the cleaning unit. The optimum electrolyzing parameters of acidic electrolyzed water (AcEW) and alkaline electrolyzed water (AlEW) were investigated using Box–Behnken experimental design. The tests were conducted at different types of electrodes (titanium, zinc, copper, and stainless steel), electrical voltages (5, 10, and 15 V), electrolysis times (5, 7.5, and 10 minutes), and NaCl concentrations (0.05, 0.53, and 1.0%). There were no obvious differences observed in the physicochemical properties of EW when different electrodes were used. However, stainless steel was chosen as it meets most of the selection criteria. The best-optimized conditions for AcEW were at 11.39 V, 0.65% NaCl, and 7.23 min, while the best-optimized conditions for AlEW were at 10.32 V, 0.6% NaCl, and 7.49 min. The bactericidal activity of AcEW and AlEW were examined against Escherichia coli ATCC 10536 at different temperatures (30°C and 50°C) for 30 s. The capability of both EWs (AcEW and AlEW) to clean stainless steel surfaces inoculated with Escherichia coli ATCC 10536 (with and without the presence of fat-based residue) was also assessed. The results show that both EWs can reduce Escherichia coli to non-detectable levels (less than 2 log CFU/ml). However, EW could not physically, and microbiologically clean the plates, which were fouled with inoculated fat-based residues, as the deposits acted as a barrier and it reduced efficacy. Thus, mechanical action (manual brushing or shear stress from rinsing effect) and hot water rinse were included in the pre-rinse steps to remove fat-based residues and ensure the surfaces were ready for the next sanitation steps (alkaline wash, acidic wash, or disinfection). A conceptual design of a portable electrolysis sanitation unit was designed based on the optimized electrolyzing parameters and the proposed sanitation program. The theory of Inventive Problem Solving (TRIZ), a systematic methodology for innovation, was applied to get the creative conceptual design ideas for the portable electrolysis sanitation unit. The portable electrolysis sanitation unit has 2 main systems: 1) electrolyzed water generation system and 2) heating and water jet system. The portable electrolysis sanitation unit can generate hot water at different water jet pressure and, at the same time, can generate AcEW and AlEW that will replace commercial sanitation solutions. Industrial-based studies using a portable cleaning unit have shown promising results and the proposed sanitation program has improved sanitation efficiency significantly. It is expected that the developed conceptual design of the portable electrolysis sanitation unit could bring more benefit to the frozen meat patty industry by reducing sanitation costs and addressing numerous sanitation issues.